Asymptotic behaviour of rapidly varying solutions of a differential equation with rapidly varying nonlinearity - Golubev, S. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.925We study the asymptotic behavior of one class of solutions for a two-term nonautonomous ordinary differential equation of the fourth order with rapidly varying nonlinearity.